RELIGIOUS ESCHATOLOGY: THE DOCTRINE OF THE COMING OF THE SAVIOR IN THE END TIMES IN THE PERSPECTIVE OF ABRAHAMIC RELIGION - Muhammad Saekul Mujahidin (Institut Agama Islam Negeri Ponorogo, 2023)
Eschatology is a doctrine or teaching related to the last days, in the Abrahamic religious belief about eschatology, namely the arrival of a savior at the end of time for these religions, namely Christianity, Judaism and Islam, the three religions believe that at the end of time a when there will be a savior who will save them from the chaos that existed in the world before the apocalypse. This issue includes who is the true savior for Christianity, Judaism, and Islam. This paper aims to find out who is the savior of the end times for the Abrahamic Religion, namely Christianity, Judaism and Islam. The form of this research uses Research from the Library (Library Research) which is carried out by collecting data including books, journals and others as well as clarifying some of the literature related to this research. According to Christianity, Jesus is their savior, who will save Christians from various corruptions in the end times, then the Jews believe in the Messiah or the Messiah as their savior in the last days, because with the messiah they can live in peace. without any interference from others, and Muslims believe in the existence of Allah's Apostle, Jesus son of Mary, who will save you Muslims from the Fitnah of Dajjal at the end of time, so Muslims need Jesus' help to kill Dajjal before the apocalypse comes.